Perceptions of support staff I of Chief Minister department (Kuching) on the factors affecting total quality management practices - Agnes, Sabang (Universiti Malaysia Sarawak (UNIMAS), 2011)
The purpose of conducting of this study is to investigate on the perceptions of Support Staff I of Chief Minister Department (Kuching) on the factors such as employees perceptions towards Total Quality Management (TQM), management commitment and leadership, employee knowledge on TQM and employees' involvement in TQM activities that affect TQM practices. Questionnaires are used as an instrument to collect the data from a sample of 177 respondents. Perception Index is be used to measure the respondent's perception on TQM) Chi-Square is used to test the statistical significance of the observed association in cross tabulation in order to determine whether a systematic association exists between the two variables. Pearson Correlation Coefficient is used to test the significance of the relationship between Perceptions of Support Staff I and factors affecting TQM practices (e.g. employees perceptions towards TQM, management commitment and leadership, employee knowledge on TQM and employees' involvement in TQM activities). It is revealed in this study that majority of the staffs have positive perceptions on TQM. Chi-Square test finding discloses that distribution of respondent perceptions towards TQM and factors affecting TQM practices is significantly different. Pearson Correlation shows that there is relationship between distribution of respondent perceptions and social demographic factors (gender, age, race, level of education and years of services). It indicates that demographic factors have moderate relationship with staff perceptions. Recommendation are made based on the finding which takes into consideration the important role played by the employees in the organization.